Pendekatan Problem Solving dengan Strategi Metakognitif untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa - Idayu Rifki Anjani (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
The purpose of this study was to describe the increase in mathematical problem-solving abilities and students' responses during the learning process by applying a problem-solving approach with metacognitive strategies. This research is a classroom action research consisting of 3 cycles. The instrument used is a test of mathematical problem-solving skills and student response questionnaire. The results of the study concluded that the ability of mathematical problem-solving in the application of problem-solving approaches with metacognitive strategies has increased. This can be seen from the average test of mathematical problem-solving ability from cycle I is 67, cycle II is 70 and cycle III is 82. While the response of students is included in the effective criteria, with a percentage of positive responses 94% and a negative response percentage of 6%.